2016
DOI: 10.3892/ol.2016.5471
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gap junction intercellular communication composed of connexin 43 on the antineoplastic effect of adriamycin in breast cancer cells

Abstract: Abstract. Gap junctions (GJs) serve the principal role in the antineoplastic (cytotoxicity and induced apoptosis) effect of chemical drugs. The aim of the present study was to determine the effect of GJ intercellular communication (GJIC) composed of connexin 43 (Cx43) on adriamycin cytotoxicity in breast cancer cells. Four cell lines (Hs578T, MCF-7, MDA-MB-231 and SK-BR-3) with different degree of malignancy were used in the study. The results of western blotting and immunofluorescence revealed that, in Hs578T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
(66 reference statements)
2
10
0
Order By: Relevance
“…Arguably, this gap junction hyperactivity (above baseline level) may signify some form of abnormality [64] or pathology. However, in a recent report by Jiang et al, it was demonstrated that high levels of Cx43-mediated gap junctional communication attenuate the degree of malignancy in multiple cancer cell lines [65]. Considering that cancer and vascular diseases share common pathology progression pathways [66], the results of the study conducted by Jiang et al can be extrapolated to suggest that over-recovery of interendothelial gap junction-mediated dye spread is not necessarily pathological and may actually be physiological beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Arguably, this gap junction hyperactivity (above baseline level) may signify some form of abnormality [64] or pathology. However, in a recent report by Jiang et al, it was demonstrated that high levels of Cx43-mediated gap junctional communication attenuate the degree of malignancy in multiple cancer cell lines [65]. Considering that cancer and vascular diseases share common pathology progression pathways [66], the results of the study conducted by Jiang et al can be extrapolated to suggest that over-recovery of interendothelial gap junction-mediated dye spread is not necessarily pathological and may actually be physiological beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence suggests that Cx43 expression levels are negatively correlated with HER2 expression [ 21 , 22 ]. Additional experimental evidence indicates that HER2+ breast cancer cell lines have reduced Cx43 expression as compared to ER+ breast cancer cells [ 23 , 24 ]. Somewhat paradoxically, the analysis presented here, suggests that high Cx43 expression levels correlates with reduced relapse free survival (RFS) in HER2-positive (HER2+) breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether the dye communication between PVMs GFP and ECs involved Cx43 GJ protein, we employed a GJ blocker, 18α-GA, which has been reported to block Cx43 mediated intercellular communication (Zhu et al, 2016;Jiang et al, 2017). As shown in Figures 2C,D, we found that blocking GJ with 18α-GA significantly blocked dye transfer from an injected PVM GFP to the connected ECs.…”
Section: Cx43 Mediation Of Pvm-ec Communication Tested In An In Vitromentioning
confidence: 86%
“…Since the Alexa dye is negatively charged, a negative potential (−10 mV) was applied to expedite diffusion of the dye. To block the GJ, 18α-Glycyrrhetinic acid (18α-GA,10 μM, G8503, Sigma-Aldrich, St. Louis, MO) was added to the culture medium for 30 min (Zhu et al, 2016;Jiang et al, 2017).…”
Section: Dye Injection With a Patch-clamp Pipettementioning
confidence: 99%